Characteristics of Ulu al-Albāb in the Qur’an (A Tahlili Study of QS al-Ra’d [13]: 19–24) - Hidayat, Rahmat; Abubakar, Achmad; Irham, Muhammad (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2023)
The Qur’an attributes specific characteristics to ulul al-albāb (those endowed with intellect). This study aims to identify these characteristics as described in QS al-Ra’d [13]: 19–24. Employing a descriptive-analytical method with a content analysis approach, this research utilizes tahlili interpretation and relies on library research for data collection. The findings reveal that the ulul al-albāb in the aforementioned verses possess distinct qualities: steadfastness in fulfilling covenants, commitment to maintaining human relationships, and perseverance in acts of worship. Furthermore, verse 24 highlights that they will be rewarded with Paradise and honored by angels.